Optimizing Neuromuscular Electrical Stimulation Pulse Width and Amplitude to Promote Central Activation in Individuals With Severe Spinal Cord Injury - Arpin, David J.; Ugiliweneza, Beatrice; Forrest, Gail; Harkema, Susan J.; Rejc, Enrico (Frontiers in Physiology, 2019)
Neuromuscular electrical stimulation (NMES) is one of the most effective treatments for counteracting the deleterious skeletal muscle adaptations that occur after spinal cord injury (SCI). Additionally, previous findings suggest that NMES can activate motor units via both peripheral and central mechanisms; however, this NMES-promoted central activation is not well understood. In this study, we aimed at investigating the effects of NMES on central activation in 10 individuals with motor complete SCI, focusing on understanding how to optimize NMES pulse width and amplitude for promoting central activation in this population. To this end, we used NMES to generate isometric contractions of the knee extensors and ankle plantarflexors while electromyographic (EMG) activity was recorded from the vastus lateralis and gastrocnemius medialis, respectively. We used EMG activity that persisted after the termination of NMES delivery (post-NMES) as a neurophysiological marker to assess central activation, and explored differences in post-NMES EMG activity promoted by 500 µs and 1000 µs pulse width NMES. Additionally, we explored the relationships between post-NMES EMG amplitude, torque output, and stimulation amplitude. Our results show that the higher pulse width (1000 µs) demonstrated a greater effect on central activation as quantified by more frequent occurrences of post-NMES EMG activity (p = 0.002) and a 3.551 µV higher EMG amplitude (p = 0.003) when controlling for the torque output generated by 500 µs and 1000 µs pulse width NMES. Importantly, we also found that the interplay among central activation, stimulation amplitude and muscle torque output differs across SCI individuals, conceivably because of the individual-specific characteristics of the cord lesion and following plasticity of the spinal circuitry. These results suggest that NMES can be optimized to promote central activation, which may lead to novel opportunities for motor function recovery after SCI.